2014
DOI: 10.1002/hfm.20577
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Measurement Method of Users’ Emotional Experiences Shopping Online

Abstract: Emotions play an important role in the design of e-commerce websites. A website should satisfy its users' emotional needs. Emotion measurement is a prerequisite to understanding users' emotional needs; because emotions contain complicated components, they are difficulty to measure. To interpret users' emotional experiences while the users are interacting with e-commerce websites, we propose a multimodal measurement method conjoint using questionnaires, eye tracking, and physiological measures. The effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Only those who had lived in Australia for all or most of their lives were included to reduce cultural effects. Physiological measurement procedures are time consuming and so such sample numbers are common (Bolls, Lang, and Potter 2001; Guo et al 2014; Ohme et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Only those who had lived in Australia for all or most of their lives were included to reduce cultural effects. Physiological measurement procedures are time consuming and so such sample numbers are common (Bolls, Lang, and Potter 2001; Guo et al 2014; Ohme et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The investigation of stimulus from dynamic environments during the actual shopping process online is limited (Huddleston et al, 2015;Tupikovskaja-Omovie & Tyler, 2018;Tupikovskaja-Omovie et al, 2015). Furthermore, the majority of previous eye tracking studies analysing fashion websites (Benn et al, 2015;Djamasbi et al 2010a,b;Gidlof et al 2012;Guo et al 2015) excluded the payment stage, which can reveal crucial usability issues of the retailer's website as well as how mobile consumers approach payment on smartphones (Tupikovskaja-Omovie & Tyler, 2018). Therefore, this paper aims to answer the following research question: What are mobile consumers' browsing and purchasing behaviour patterns in fashion m-retail?…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the difference in saccade count can also be explained in terms of players' evaluations of an interactive interface. In the context of a shopping website, Guo [40] conducted an eye-movement experiment and found that the users' emotional evaluation of the shopping website was significantly negatively correlated with the saccade count, that is, the high valence and arousal shopping website would induce a smaller saccade count among users. In this case, the game interface with high interactive experience was bound to bring a high level of emotional experience to the player, especially when the player browsed the game interface for the first time, the participant had a rational understanding of the appearance of the navigation interface within 20 s of free browsing.…”
Section: The Eye-movement Indicator Reflecting Interactive Experiencementioning
confidence: 99%